Perencanaan Pembangunan Pelabuhan di Muara Sungai Bondoyudo - Galuh, Senki Desta; Yanuar, Setiyo Ferdi; Kuryanto, Totok Dwi; Ahmad, Hilfi Harisan; Dewi, Ilanka Cahya (Portal: Jurnal Teknik Sipil, 2024)
The development of transportation infrastructure aims to reduce disparities between regions and encourage equal distribution of development results. Sedimentation is calculated based on the amount of sediment transported and the ratio of the amount of sediment flowing through the river section per unit time, and is based on the area of the river basin. To simplify calculations, analysis can be carried out based on nine river geomorphological variables, such as main direction of flow (X), time (t), water discharge (Q), sediment transport (S), river channel width (B), river channel depth (h ), river gradient (i), sediment diameter (D), and river bed coefficient (C). Precast concrete is a concrete material that is produced in a factory and the concrete is transported and installed at the building construction site. Flyslab concrete products, which are factory-made precast concrete, consist of a mixture of building materials of various sizes according to standards set by the company. Using precast concrete as the main material can make construction time faster.